A systematic review of interventions to increase the use of standardized outcome measures by rehabilitation professionals. (March 2017) - Colquhoun, Heather L; Lamontagne, Marie-Eve; Duncan, Edward AS; Fiander, Michelle; Champagne, Catherine; Grimshaw, Jeremy M
Objective: To determine the types and effectiveness of interventions to increase the knowledge about, attitudes towards, and use of standardized outcome measures in rehabilitation professionals. Data sources: An electronic search using Medline, EMBASE, PsycINFO, CINAHL, Ergonomics Abstracts, Sports Discus. The search is current to February 2016. Study selection: All study designs testing interventions were included as were all provider and patient types. Two reviewers independently conducted a title and abstract review, followed by a full-text review. Data extraction: Two reviewers independently extracted a priori variables and used consensus for disagreements. Quality assessment was conducted using the Assessment of Quantitative Studies published by the Effective Public Health Practice Group. Data synthesis: We identified 11 studies involving at least 1200 providers. Nine of the studies showed improvements in outcome measure use rates but only three of these studies used an experimental or quasi-experimental design. Eight of the studies used an educational approach in the intervention and three used audit and feedback. Poor intervention description and quality of studies limited recommendations. Conclusions: Increased attention to testing interventions focused on known barriers, matched to behavior change techniques, and with stronger designs is warranted.